Isolamento, identificação e avaliação do potencial de leveduras como agentes de proteção de plantas de feijoeiro ao crestamento bacteriano comum - Heling, Anderson Luis (2016)
Various organisms can be used for biological control and host plant resistance induction to pathogens, among them, the yeasts. This study aimed to insulation and identify yeasts residents of phyloplan, test the potential of these insulator in production of volatile and non-volatile composts which can interfere with the development of colonies of X. axonopodis pv. phaseoli in vitro, and test these insulators in vivo in a greenhouse, for its effect on the severity of the common bacterial blight in beans, and also evaluate other factors related to productivity. The insulation of the yeast was carried from leaf and floral tissues of plants grown in environments, free use of pesticides. The identification of the insulator was based on biochemical tests and whose profile was compared to CBS-Knaw Fungal Biodiversity Centre. To evaluate the aggression of the insulator, was evaluated the production of volatile and non-volatile pairing and cultures. In a greenhouse all insulators were tested on bean plants where applied treatments on leaves and inoculated the pathogen on all leaf as well as in the first trifoliate. The severity of the common bacterial blight was evaluated in both sheets to verify that occurred the biological control of the disease and/or a possible induction of resistance. Based on this test was selected six insulators to be tested in the field in the dry season (2014/2015) and in rainy season (2015/2016), so that, there were three applications of treatments in all air part of the treated plants, and evaluated the severity of blight common bacterial as well as factors related to productivity. There was obtained 54 yeasts insulators, 42 of these were identified. All isolates showed in vitro production of non-volatile compounds capable of reducing the development of colonies of X. axonopodis pv. phaseoli. Of the 54 isolates, 47 had production of volatile compounds, in vitro, and were able to reduce the development of pathogen colonies. In greenhouse, 35 isolates had control of common bacterial blight. The Isolates Zygoascus hellenicus AH 05-5 and Rhodotorula aurantiaca AH12-3 promoted an induction susceptibility to disease. The Isolates Cryptococcus laurentii AH 01-1, Rhodotorula glutinis AH 14-3 and Sporidiobolus johnsonii AH 16-1 had reduced AUDPC of common bacterial blight in bean plants grown in the field, however, the control of this disease did not result in increased productivity